A randomised controlled trial comparing telephone review with face to face consultations in the management of adult asthmatics in UK primary care - Pinnock, H (Prim Care Respir J, 2002)
INTRODUCTION: Current UK Asthma Guidelines emphasise the importance of regular review. However, only a third of adult asthmatics attend for an annual review despite significant morbidity. This study tests the hypothesis that a telephone review is an effective and safe alternative to face-to-face consultations. METHODS: Symptomatic (definition: one or more bronchodilator prescription in past 6 months) asthma patients not reviewed in the previous 12 months were recruited from four UK general practices and centrally randomised to telephone review or face-to-face consultation with the asthma nurse. Our primary outcome measure was the proportion of asthmatics reviewed. Other outcomes of interest were: length of consultation, asthma quality of life (measured using validated Juniper Mini Asthma Quality of Life Questionnaire (miniAQLQ)) and patient satisfaction (measured using validated Nursing Care Satisfaction Questionnaire (NCS)). RESULTS: 278 asthmatics were randomised to surgery (S: n=141) or telephone (T: n=137) assessment. Baseline demographic characteristics were similar in both groups. 101 (74%) of asthmatics in the telephone group were reviewed compared to 68 (48%) in the surgery group (p<0.001) Telephone consultations were significantly shorter (mean duration S: 21.87 (SD 6.85) vs.T: 11.19 (SD 4.79) minutes (p<0.001). Quality of life measured three-months after the assessment was equivalent in the two groups: miniAQLQ S: 5.22 (SD 1.14) vs. T: 5.15 (SD 1.28) p=0.69. Both groups were equally satisfied with the consultation NCS: S: 3.86 (SD 0.55) vs. T: 3.80 (SD 0.57), p=0.51 CONCLUSION: Telephone consultations enabled 26% (95% CI 14 to 37%, p<0.001; NNT=3.8) more asthmatics to be reviewed than surgery consultations without any apparent clinical disadvantage or loss of satisfaction. The shorter duration of telephone consultations suggests that this may be an efficient option for the routine review of asthmatics. FUNDING: British Lung Foundation (Grant No P00/9) Aziz Sheikh is supported by a NHS R&D National Primary Care Fellowship.